Trade shocks and youth jobs - Michael Olabisi (IZA Journal of Labor Policy, 2020)
This paper examines the impacts of trade on youth employment in the United States. The overarching goal is to link lessons from the decline of manufacturing jobs in the past decades to future prospects for the US economy. We find higher rates of job losses with exposure to import competition for US youth, than for older workers. Our analysis uses buyer-supplier relationships between sectors of the US economy to show that the direct effects of trade on the importing sectors underrepresent the impact of trade on jobs.
Keywords: F14; J21; 330; Youth Employment; Trade Shocks; Sector Linkages